Provincial Government Policies in Improving the Quality of Madrasah Diniyah Teachers in East Java: Kebijakan Pemerintah Provinsi dalam Peningkatan Kualitas Guru Madrasah Diniyah Di Jawa Timur - Anwar, Najih (Halaqa: Islamic Education Journal, 2021)
This article aims to determine the background and objectives of provincial government policies in improving the quality of Madrasah Diniyah teachers in East Java, Indonesia. The management of Islamic Education institutions is the authority and responsibility of the Ministry of Religion, however, the East Java provincial government has a moral responsibility to participate in developing Islamic education institutions, namely Madrasah Diniyah through policies to improve the quality of Madrasah diniyah teachers. This research method uses qualitative research with a case study approach and research design using descriptive-analytic. The research findings are: 1) The reality of Diniyah Madrasah teachers in East Java, there are still many who have not met the qualifications as mandated in the Teacher and Lecturer Law. 2) The Provincial Government of East Java made a policy to improve the quality of madrasah diniyah teachers due to social and political factors.